On Flows Spectrum on Closed Trio of Contours with Uniform Load (European Journal of Pure and Applied Mathematics, 2018)
Considered dynamical system is a flow of clusters with the same length $l$ on contours of unit lengthconnected in polar-remote points into closed chain.When clusters move trough common node, the left-priority rule of conflict resolution works.In the paper it is shown that in the case of chain consisted third contours the dynamical system has a spectrum of velocity and mode periodicity consisted on not more two components.Distribution of spectrum in dependence on load $l$ is developed.Hypothesis on discrete spectrum in the case of arbitrary number of contours are formulated.
Keywords: Dynamical System; Spectrum; Self-organization; Contour Graph; Collapse; Cluster Model